2017
DOI: 10.4269/ajtmh.17-0545
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Cluster of Three Leptospirosis Cases in a New York City Abattoir and an Unusual Complication in the Index Case

Abstract: We report the case of a 46-year-old male abattoir worker who developed myalgias, shortness of breath, and irritability 2 weeks after sustaining a laceration to the hand with a knife at work. During his hospital evaluation for septic shock he was noted to be febrile, hypotensive, profoundly jaundiced with aseptic meningitis, and renal failure, and was diagnosed with infection confirmed by serum and urinepolymerase chain reaction. After standard antibiotic therapy and recovery from severe clinical illness, he de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Through literature search, we realized that antibiotics related to the development of JHR not only include penicillins, tetracyclines and erythromycin, but also newer antimicrobial agents such as cephalosporins, levofloxacin, ciprofloxacin, clarithromycin, meropenem, and azithromycin can also cause JHR [ 1 ]. To prove the relationship between leptospirosis and JHR and predict the characteristics of patients with severe types, we searched and reviewed the presentation of five adults with pulmonary hemorrhagic leptospirosis, and found that they all showed aggravation of existing symptoms or the occurrence of new symptoms that cannot be explained by the progression of the disease [ [2] , [3] , [4] , [5] , [6] ]. However, they survived after active symptomatic treatment ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through literature search, we realized that antibiotics related to the development of JHR not only include penicillins, tetracyclines and erythromycin, but also newer antimicrobial agents such as cephalosporins, levofloxacin, ciprofloxacin, clarithromycin, meropenem, and azithromycin can also cause JHR [ 1 ]. To prove the relationship between leptospirosis and JHR and predict the characteristics of patients with severe types, we searched and reviewed the presentation of five adults with pulmonary hemorrhagic leptospirosis, and found that they all showed aggravation of existing symptoms or the occurrence of new symptoms that cannot be explained by the progression of the disease [ [2] , [3] , [4] , [5] , [6] ]. However, they survived after active symptomatic treatment ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, sporadic cases have occurred in people exposed to rat urine [7]. Three cases with exposure to a rodent infested environment were identified during 2017 confined to one block in the Bronx, New York area [8]. Our patient comes from urban NYC, and had a rat infestation of her house, which likely explains the disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Humans contract the disease through contact with the urine of infected animals or environmental sources, such as lakes and rivers, contaminated with Leptospira [ 4 ]. In the United States, where the disease is rarely recognized [ 4 , 5 ], infections have been associated with occupational exposure to infected animals [ 6 , 7 ], recreational exposures such as swimming [ 8 ], and individuals living in economically disadvantaged urban inner-city environments [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%